Jaminan Konsumsi Rumah Tangga Petani Sagu di Desa Sungai Tohor Kabupaten Meranti, Riau - M.Rawa El Amady (Universitas Padjadjaran, 2017)
This study addresses the culture of debt as the socio-economic security of daily consumption sustainability of rural households in Sungai Tohor Village, Meranti Riau District. The village has become the target of many development programs from various institutions which focus on peat restoration and sago cultivation. Despite the programs, however, the number of poor household during and after the programs increased; from 30 households in 2015 to 50 households in 2016. This study aims at answer the question